Efficient polymalic acid production from corn straw hydrolysate by detoxification of phenolic inhibitors - Xia, Jun; Qiu, Zhongyang; Ma, Shibiao; Liu, Qianqian; Han, Renxian; Liu, Xiaoyan; Xu, Jiaxing (Frontiers in Bioengineering and Biotechnology, 2023)
Inhibitory compounds generated from lignocellulose pretreatment would inhibit Poly(malic acid) (PMA) production by Aureobasidium pullulans, but the tolerance mechanism of A. pullulans to lignocellulosic inhibitor is poorly understood. In this study, the cellular response of A. pullulans to lignocellulosic inhibitor stress was studied. Among the three groups of inhibitors (furans, weak acids and phenolic aldehydes), phenolic aldehyde was the dominant inhibitor for PMA production.Phenolic aldehyde was mainly converted into phenolic alcohol by A. pullulans, and phenolic alcohol also exhibited severe inhibition on PMA production. Furthermore, the effect of detoxification methods on inhibitor-removal and PMA fermentation was investigated, both CaCO 3 and overliming presented poor detoxification effect, whereas resin H103 could remove both furan derivatives and phenolic compounds efficiently, thereby producing 26.27 g/L of PMA with a yield of 0.30 g/g in batch fermentation. This study will be beneficial for the development of PMA production from lignocellulosic biomass.